PENINGKATAN HASIL BELAJAR MATEMATIKA MELALUI PEMBELAJARAN KOOPERATIF TIPE JIGSAW SISWA KELAS X DKV 1 DI SMK NEGERI - PUSPITASARI, MARIA (EDUCATOR : Jurnal Inovasi Tenaga Pendidik dan Kependidikan, 2024)
This research is a Classroom Action Research (CAR) which aims to improve the learning outcomes and mathematics learning activities of class X DKV 1 students at SMK Negeri 1 Gegerbitung in the 2024/2025 academic year through Jigsaw cooperative learning. This research was conducted collaboratively and participatively which was implemented in two cycles. Data collection in this study was carried out using participant observation and written tests. Based on the results of the study, it was concluded that through jigsaw cooperative learning, it can improve the learning outcomes of class X DKV 1 students and the learning activities of class X DKV 1 students in mathematics. This is supported by research data which shows an increase in the percentage of completion of the Mathematics learning outcome test. At the time of pre-research, the students' completeness was only 39%, after implementing cycle I with the Jigsaw cooperative learning model, the percentage of completeness of learning achievement of class X DKV 1 students was 67% with an average completeness reaching 73.75, then in cycle II, the completeness of learning outcomes reached 89% with an average of 81.11. Through Jigsaw type cooperative learning, it can also improve the learning activities of class X DKV 1 students at SMK Negeri 1 Gegerbitung in the 2024/2025 Academic Year. In cycle I, the learning activities of class X DKV 1 students obtained a final score of 65%, meaning that the learning activities of class X DKV 1 students were in the good criteria. In cycle II, the final score of the learning activities of class X DKV 1 students reached 88% so that it was in the very good criteria. ABSTRAKPenelitian ini merupakan Penelitian Tindakan Kelas (PTK) yang bertujuan untuk meningkatkan hasil belajar dan aktivitas belajar matematika siswa kelas X DKV 1 di SMK Negeri 1 Gegerbitung tahun pelajaran 2024/2025 melalui pembelajaran kooperatif tipe Jigsaw. Penelitian ini dilakukan secara kolaboratif dan partisipasif yang dilaksanakan dalam dua siklus. Pengumpulan data dalam penelitian ini dilakukan dengan menggunakan observasi partisipan dan tes tertulis. Berdasarkan hasil penelitian disimpulkan bahwa melalui pembelajaran kooperatif tipe jigsaw dapat meningkatkan hasil belajar siswa kelas X DKV 1 serta aktivitas belajar siswa kelas X DKV 1 pada mata pelajaran matematika. Hal ini didukung dengan data penelitian yang menunjukkan menunjukkan adanya peningkatan persentase ketuntasan tes hasil belajar Matematika. Pada saat pra penelitian, ketuntasan peserta didik hanya 39%, setelah dilaksanakan siklus I dengan model pembelajaran kooperatif tipe Jigsaw persentase ketuntasan prestasi belajar siswa kelas X DKV 1 sebesar 67% dengan rata-rata ketuntasan mencapai 73,75, kemudian pada tindakan siklus II, ketuntasan hasil belajar mencapai 89% dengan rata-rata 81,11. Melalui pembelajaran kooperatif tipe Jigsaw juga dapat meningkatkan aktivitas belajar siswa kelas X DKV 1 di SMK Negeri 1 Gegerbitung Tahun Pelajaran 2024/2025. Pada siklus I aktivitas belajar siswa kelas X DKV 1 memperoleh skor akhir 65%, artinya aktivitas belajar siswa kelas X DKV 1 berada pada kriteria baik. Pada siklus II skor akhir aktivitas belajar siswa kelas X DKV 1 mencapai 88% sehingga berada pada kriteria sangat baik.